THE RECENT STRUCTURE AND THE ASSUMED HISTORY OF FORMATION OF THE CRUST IN THE SOUTH-EASTERN SEGMENT OF THE NORTH ASIAN CRATON ALONG REFERENCE PROFILE 3-DV - E. Yu. Goshko (Geodinamika i Tektonofizika, 2015)
The article presents results of specialized processing of the deep seismic profile along a part of Reference Profile 3-DV which crosses the Aldan-Stanovoi shield in the meridian direction and goes across its buried northern slope. The study is aimed at determining frequency-energy characteristics of the seismic wave field which are related to physical conditions of geological features of the crust. Based on analysis and interpretation of the dynamic profiles, it is possible to reveal and contour the Archean cores of consolidation of the Aldan shield and its buried continuation that is covered by sediments of the Middle Lena monocline and to input new facts in the proposed geodynamic model showing formation of the crust in the south-eastern segment of the North Asian craton.